Analysis of aroma and polyphenolic compounds in Saperavi red wine vinified in Qvevri. Issue 12 (19th October 2021) - Ieri, Francesca; Campo, Margherita; Cassiani, Chiara; Urciuoli, Silvia; Jurkhadze, Ketie; Romani, Annalisa
Abstract: The purpose of this study is to analyze and characterize a Georgian red wine from Saperavi grape, obtained in Qvevri (Georgian traditional winemaking method), by using innovative techniques for the determination of the polyphenolic content, aroma, and its correlation to the sensory characteristics. This peculiar red wine, after high‐performance liquid chromatography with diode‐array detection and mass spectrometry (HPLC‐DAD‐MS), headspace solid‐phase microextraction–gas chromatography–mass spectrometry (HS‐SPME‐GC‐MS), and HS‐SPME‐GCxGC‐MS/TOF (two‐dimensional gas chromatography) chemical characterization showed a high polyphenol content (19.6 × 10 2  mg/L, 38.4% anthocyanins) and a wide range of volatile compounds, among which terpenes were associated with the aroma of flowers, lemongrass, and wood. Analyses were also conducted to determine the total polyphenol content correlated to antioxidant activity with the Folin–Ciocalteu spectrophotometric in vitro method (4.650 g GAE/L). In conclusion, for the first time on Saperavi wine, innovative techniques such as HPLC‐DAD‐MS, GC‐MS, and GCxGC‐MS/TOF were simultaneously applied in association with the traditional analytic techniques to perform a complete chemical characterization. These activities are part of a project about circular viticulture in the Georgian territory that will lead the production of traced quality wines and the valorization of the Georgian wine sector. Abstract : BLURB FOR ETOC:Analysys and characterization of a Georgian red wine from Saperavi grape, obtained in Qvevri (Georgian traditional winemaking method), by using innovative techniques for the determination of the polyphenolic and key volatile compounds to produce traced quality wines and the valorisation of the Georgian wine sector.